Discretion rather than rules: Equilibrium uniqueness and forward guidance with inconsistent optimal plans - Jeffrey R. Campbell; Jacob P. Weber (Federal Reserve Bank of Chicago, 2018)
New Keynesian economies with active interest rate rules gain equilibrium determinacy from the central bank's incredible off-equilibrium-path promises (Cochrane, 2011). We suppose instead that the central bank sets interest rate paths and occasionally has the discretion to change them. Private agents taking future central bank actions and their own best responses to them as given reduces the scope for self-fulfilling prophecies. With empirically-reasonable frequencies of central-bank reoptimization, the monetary-policy game has a unique Markov-perfect equilibrium wherein forward guidance influences current outcomes without displaying a forward-guidance puzzle.
Keywords: E12; E52; 330; Monetary Policy; Open Mouth Operations; Quasi-Commitment; Ramsey Problem